DEVELOPMENT OF PEDAGOGICAL SKILLS IS AN IMPORTANT FACTOR IN THE FORMATION OF THE COGNITIVE CHARACTERISTICS OF THE TEACHER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses an important factor in the reform of the public education system of the country - the pedagogical skills of teachers, the development of their cognitive characteristics, ways and means to achieve this, the specifics of the process of professional development of teachers, some aspects of its reform. described in detail.